Comparative Evaluation of Forsythiae Fructus From Different Harvest Seasons and Regions by HPLC/NIR Analysis and Anti-inflammatory and Antioxidant Assays - Qian Qu (Frontiers Media S.A., 2021)
Forsythiae Fructus (FF), the dry fruit of Forsythia suspensa (Thunb.) Vahl, has a long history of use in traditional Chinese Medicine for its heat-clearing and detoxifying properties. It possesses clinical therapeutic effects and biological functions showing efficacy in handling different diseases. To investigate the FF differences in Henan, Shanxi, and Shaanxi in August and October, the surface morphology, mid-infrared and near-infrared spectrums, and HPLC were analyzed. Concurrently, the anti-inflammatory and antioxidant effects on LPS-induced J774A.1 cells were evaluated by western blot and RT-qPCR. The results showed that FF from different Harvest Seasons and Regions are provided with different microstructures and mid-infrared and near-infrared spectrums, and the levels of forsythiaside A and phillyrin of FF from Shanxi in August and phillygenin of FF from Shaanxi in August were the highest. Meanwhile, FF from Shanxi and Shaanxi in August markedly reduced the levels of inflammatory cytokines and mediators (TNF-α, IL-1β, NF-κB, and iNOS) and the protein expression levels of phosphorylated total IKKα/β and nuclear NF-κB. In August, SXFF and SAXFF also promoted the mRNA expression levels of HO-1 and NQO1 and the protein expression levels of HO-1 and nuclear Nrf2 and suppressed the protein expression levels of KEAP1. Spearman correlation analysis showed that phillygenin had a strong correlation with the protein expression on LPS-induced J774A.1 cells. In summary, our results showed that FF from harvest seasons and regions contributed to the distinct differences in microstructure, the mid-infrared and near-infrared spectrums, and compound content. More importantly, FF from Shanxi and Shaanxi in August showed marked anti-inflammatory and antioxidant activities, but with some differences, which may be because of different contents of phillygenin and phillyrin of lignans in FF.